2019
DOI: 10.1002/dac.4185
|View full text |Cite
|
Sign up to set email alerts
|

A simple void node and loop‐free three‐dimensional routing protocol for multi‐hop wireless networks

Abstract: SummaryWireless networks are now very essential part for modern ubiquitous communication systems. The design of efficient routing and scheduling techniques for such networks have gained importance to ensure reliable communication. Most of the currently proposed geographic routing protocols are designed for 2D spatial distribution of user nodes, although in many practical scenarios user nodes may be deployed in 3D space also. In this paper, we propose 3D routing protocols for multihop wireless networks that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…3,4 The local minimum problem in 3D position-based geographical routings has been studied by many researchers in the last few years. Begum and Hussain 5 have proposed a void node and loop management technique for 3D multi-hop wireless networks. Many position-based geographic routing protocols [6][7][8][9][10][11][12] have been proposed by the researchers in the last few decades, most of those were designed for two-dimensional spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The local minimum problem in 3D position-based geographical routings has been studied by many researchers in the last few years. Begum and Hussain 5 have proposed a void node and loop management technique for 3D multi-hop wireless networks. Many position-based geographic routing protocols [6][7][8][9][10][11][12] have been proposed by the researchers in the last few decades, most of those were designed for two-dimensional spaces.…”
Section: Introductionmentioning
confidence: 99%
“… In the proposed work, routing paths are calculated in 3D space. Among all the nodes within the transmission range of the source/user, the node that forms a minimum angle with the reference line (RL) drawn from itself to the base station/destination is selected as an intermediate relay node to reach the base station. We have proposed projection methods to project the routing paths obtained in 3D space to the RL and various planes. The proposed projection technique projects the IM nodes of the obtained route in 3D space on the main RL drawn from sender/user to destination/base station. The proposed projection method projects the route obtained in 3D space on three 2D planes XY, YZ, ZX and a particular 3D plane. The proposed projection methods simplify the operational difficulties with the routes in 3D space and enhance the network performance in terms of throughput, delay and energy expenditure. The performance of proposed technique are evaluated through extensive simulation then compared with some popular existing protocols 2,5,34 It is found that the performance of proposed projection technique outperforms the existing routing protocols. …”
Section: Introductionmentioning
confidence: 99%